The Effects of Three Teaching Methods of Lecture Training Game and Role Playing on knowledge and Practice of Middle School Girls in Regard to Puberty Nutrition - Seied Mohammad Mehdi Hazavehei; Mohammad Hosein Taghdisi; Hamid Reza Mohaddes; Akbar Hasanzadeh (Kerman University of Medical Sciences, 2007)
Background : Suitable nutrition is an important aspect in every stage of life particularly in puberty stage of females One of the important priorities of medical education is improving the quality of educational programs in regard to the puberty nutrition in middle school girls Objective: The aim of this study was to determine and compare the effects of three teaching methods of lecture training games and role playing on knowledge and practice of middle school girls in regard to puberty nutrition Methods : In this quasiexperimental research six first grade classes from girls middle schools of four distracts in Mashhad were selected randomly The students of these classes (n=174) were randomly divided into three groups of lecture (taught by giving lecture) game (taught by playing games) and role playing (taught by role playing) Each group participated in two 45minute training sessions about puberty nutrition The students knowledge and practice were evaluated by acceptable valid and reliable questionnaire and checklist before immediately after and one month after the training sessions Results : According to the results mean (±standard deviation) knowledge scores of students immediately after intervention were 499 (±115) in lecture group 57 (±89) in game group and 61 (±12) in role playing group that showed significant increase [respectively 201 (±116) 29 (±11) and 305 (±115)] compared to before the intervention Mean knowledge score immediately after and one month after holding training sessions were significantly different in all three groups (P